Prompting Children’s Belief Revision About Balance Through Primary and Secondary Sources of Evidence - Larsen, Nicole E.; Venkadasalam, Vaunam P.; Ganea, Patricia A. (Frontiers in Psychology, 2020)
Prior evidence has shown that children’s understanding of balance proceeds through stages. Children go from a stage where they lack a consistent theory (No Theory), to becoming Center Theorists at around age 6 (believing that all objects balance in their geometric center), to Mass Theorists at around age 8, when they begin to consider the distribution of objects’ mass. In this study we adapted prior testing paradigms to examine 5-year-olds’ understanding of balance and compared children’s learning about balance from evidence presented through primary sources (a guided activity) or secondary sources (picture books). Most of the research on young children’s understanding of balance has been conducted using a single object, weighted either proportionally (symmetrical object) or disproportionally (asymmetrical object). In this study, instead of using a single object, 5-year-olds (N = 102) were shown 4 pairs of objects, two with the same weight and two with different weight. Children were told to place the objects on a beam where they thought they would balance. We found evidence for an intermediate level of understanding. Transition Theorists represent children who have two distinct theories, one for balancing same weight objects, and one for balancing different weight objects, but one of these theories is incorrect. Following the assessment of children’s understanding, we compared their learning about balance from evidence that was either presented through primary sources (a guided activity) or secondary sources (picture books). Children learn equally well from both sources of evidence. Findings are discussed in terms of theoretical and practical implications.